Multilevel Inverter Control Circuit Based on DSP-FPGA Coprocessor - Muhammad Imran Ahmad (School of Computer & Communication Engineering, 2008)
Ekspo ini berlangsung di Dewan Sek. Men. Putra, Kangar, Perlis.